EFEKTIVITAS PEMBERIAN JAHE (Zingiber officinale) SEBAGAI ANTIEMETIK PADA IBU HAMIL - Hasna, Annajmi; Nurunnisa, Shinta; Syami, Danial; Izzati, Olivia Nolisviani; Aristya, Davina Aqiilah; Wibowo, Arif Difan Satria; Anjani, Rr. Berliana Putri Dyah; Wahyudin, Wahyudin (Fakultas Kedokteran Universitas Jenderal Soedirman, 2024)
Nausea and vomiting during pregnancy are common occurrences in the first trimester. This can be attributed to an increase in estrogen and progesterone hormones produced by human chorionic gonadotropin (HCG) in the placenta. Various therapies can be employed as antiemetics in pregnant women, and one of them is traditional therapy involving the administration of ginger extract. This research design uses a literature review methodology, gathering data from international and national journals that meet the inclusion and exclusion criteria. The databases utilized include Google Scholar, PubMed, and Garuda. To understand the effectiveness of ginger extract administration as an antiemetic in pregnant women. The methodology employed is a literature review, utilizing the Google Scholar database to search for articles published between 2013 and 2023 in both Indonesian and English languages. Ginger can reduce nausea and vomiting by modulating gastrointestinal effects such as smooth muscle contractions and stimulating gastric motility. It inhibits 5-HT3 receptors in the central nervous system, hampers carminative effects, reduces cisplatin effects, and has effects similar to dimenhydrinate. Administering ginger infusion twice a day for 4-7 days has shown a decrease in the occurrence of nausea and vomiting in pregnant women. Additionally, ginger aromatherapy with 5 ml for four consecutive days can reduce the incidence of nausea and vomiting in pregnant women with hyperemesis gravidarum. Ginger extract can reduce nausea and vomiting in pregnant women.